Forensic features and genetic structure of the Hotan Uyghur inferred from 27 forensic markers. (17th November 2019) - Chen, Pengyu; Zou, Xing; Wang, Mengge; Gao, Bo; Su, Yongdong; He, Guanglin
Abstract: Background: The Uyghur is the fifth largest group in China and also the largest ethnic minority in Xinjiang. Aim: To explore the genetic variations of 27 forensic genetic markers included in the newly developed SureID ® PanGlobal Human DNA Identification System and analyse the genetic relationship between Xinjiang Uyghur and their neighbours. Subjects and methods: We genotyped 27 markers in 2, 189 unrelated Uyghur individuals from the Hotan Prefecture in Southwest Xinjiang. Comprehensive population genetic studies among Chinese populations and worldwide populations were conducted via various statistics. Results: The combined power of discrimination (CPD) and the combined power of exclusion (CPE) of the new-generation autosomal STR amplification system in the Hotan Uyghur are 9, 9999-E01 and 9, 9999-E01, respectively. Population genetic studies indicate that the Hotan Uyghur show a close genetic relationship with geographically different Uyghurs and Kazakhs, while significant genetic differentiation exists between the Hotan Uyghur and some ethnicities from other non-Turkic-speaking populations. The results of population comparisons among the 52 worldwide populations demonstrate that geographically approached intercontinental populations have close genetic relationships. Conclusions: 24 autosomal STRs are highly polymorphic and informative in the Uyghur and this system is suitable for forensic personal identification and paternity testing. Our findings not only reveal that Chinese Uyghur is a homogenous population based on forensic genetic markers, but also indicate that population genetic affinity is closely related to the adjacent populations with common ethnic origin.